2008
DOI: 10.1016/j.gep.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

An in situ hybridization-based screen for heterogeneously expressed genes in mouse ES cells

Abstract: We previously reported that Zscan4 showed heterogeneous expression patterns in mouse embryonic stem (ES) cells. To identify genes that show similar expression patterns, we carried out highthroughput in situ hybridization assays on ES cell cultures for 244 genes. Most of the genes are involved in transcriptional regulation, and were selected using microarray-based comparisons of gene expression profiles in ES and embryonal carcinoma (EC) cells versus differentiated cell types. Pou5f1 (Oct4, Oct3/4) and Krt8 (En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 44 publications
3
57
0
Order By: Relevance
“…Consis- Figure S1D), suggesting that Zscan4f accelerated the reprogramming process. We also cloned another analogous gene, Zscan4c, which is transcribed predominantly in ESCs [23,36], and showed that it has a similar activity during iPS cell generation (Supplementary information, Figure S1E). Furthermore, endogenous Zscan4 was expressed at a low level in MEFs before and after introduction of OSKM or OSKMZ (Supplementary information, Figure S1F).…”
Section: Zscan4 Improves Genomic Stability During Reprogrammingmentioning
confidence: 99%
“…Consis- Figure S1D), suggesting that Zscan4f accelerated the reprogramming process. We also cloned another analogous gene, Zscan4c, which is transcribed predominantly in ESCs [23,36], and showed that it has a similar activity during iPS cell generation (Supplementary information, Figure S1E). Furthermore, endogenous Zscan4 was expressed at a low level in MEFs before and after introduction of OSKM or OSKMZ (Supplementary information, Figure S1F).…”
Section: Zscan4 Improves Genomic Stability During Reprogrammingmentioning
confidence: 99%
“…Interestingly, mouse embryonic stem cells (ESCs) maintained in an undifferentiated state exhibit fluctuating expression of Rhox6 and/or Rhox9 (Carter et al, 2008). In addition, mouse ESCs can give rise to germ cells in vitro by manipulating the chemical composition of the culture media and by maintaining ESCs as cellular aggregates, specifically as embryoid bodies (EBs), which mimics the gastrulation process in developing embryos (Geijsen et al, 2004;Young et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several groups have performed expression microarray analyses at the single-cell level and have revealed populations of cells that differ in their transcript profiles (Crino et al, 1998;Chiang & Melton, 2003;Kurimoto et al, 2006;Ramos et al, 2006;Tang et al, 2010). Several studies, including ours, have found that well-maintained mouse ESC cultures consist of a small percentage of cells that show fluctuating expression levels of genes such as Dppa3 (Stella/Pgc7; Payer et al, 2006;Hayashi et al, 2008), Nanog (Chambers et al, 2007;Singh et al, 2007), Pecam1 (Furusawa et al, 2004;Furusawa et al, 2006), Rex1 (Toyooka et al, 2008) and Zscan4 (Falco et al, 2007;Zalzman et al, 2010), or genes associated with cell differentiation, such as Brachyury/T (Suzuki et al, 2006a;Suzuki et al, 2006b), Rhox6/9 (Carter et al, 2008), Tcf15 and Twist2 (Tanaka et al, 2008). These genes are either downregulated (Nanog and Rex1) or expressed (the rest) in about one-tenth of cells in culture as a steady state ( Fig.…”
Section: Transcriptional Heterogeneity In Pluripotent Stem Cellsmentioning
confidence: 75%